2016
DOI: 10.1097/nmd.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Childhood Trauma and Its Influence on the Course of Illness in First-Episode Psychosis

Abstract: Persons with schizophrenia spectrum disorders often report high levels of childhood trauma, which often exacerbates symptoms and impede the process of recovery. However, little is known about how these traumas are experienced by service users and how they are integrated in their life stories. To examine this, we conducted in-depth interviews with 15 service users with a diagnosis of a first-episode nonaffective psychosis who had reported 1 or more childhood traumas in self-report measures. There was an unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
(52 reference statements)
6
9
0
Order By: Relevance
“…By contrast, patients who integrated could be observed to work on making sense of such episodes. A similar process was noted by Jansen et al (2016) in a study of individuals who had experienced childhood trauma. In similar fashion to illusory mental health, an individual who coped with emotionally difficult memories by sealing over might appear, on a symptom measure to be 'well'.…”
Section: A Psychoanalytic Perspective On Paradoxical Outcomesupporting
confidence: 75%
“…By contrast, patients who integrated could be observed to work on making sense of such episodes. A similar process was noted by Jansen et al (2016) in a study of individuals who had experienced childhood trauma. In similar fashion to illusory mental health, an individual who coped with emotionally difficult memories by sealing over might appear, on a symptom measure to be 'well'.…”
Section: A Psychoanalytic Perspective On Paradoxical Outcomesupporting
confidence: 75%
“…As well as using substances, dilemmas regarding personal relationships (Jansen et al, 2016), seeking support or treatment (Connell et al, 2015; Tanskanen et al, 2011), and disclosing details about mental health difficulties (Connell, Schweitzer, & King, 2014) were described. For example, in this quote, the participant’s dilemma about taking medication appears to be a source of distress:I get depressed that I’m on an antipsychotic.…”
Section: Resultsmentioning
confidence: 99%
“…Children use their parents for support and most of the assessed adversities happened within the home-environment (Trauelsen et al, 2015), making it likely that these factors were associated. It may have been difficult to obtain support in an abusive and/or neglectful home environment (Jansen et al, 2015) and it is possible that there was a conceptual overlap between adult support and adversity. Adult support was correlated with number of adversities, post-hoc analysis: r s (93) = −0.44, p < 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that childhood adversity that has not been dealt with and may even still be happening to some degree makes it difficult to see the family. A qualitative study of our FEP group actually found that some mention that it can make them feel bad to spend time with their family (even though they love them) (Jansen et al, 2015).…”
Section: Social Supportmentioning
confidence: 99%